Modulation of homosynaptic depression during voluntary contraction and muscle fatigue with different test reflex size - Rei Takahashi; Takashi Endoh; Tsuyoshi Nakajima; Tomoyoshi Komiyama (Japanese Society of Physical Fitness and Sports Medicine, 2013)
The Hoffmann (H-) reflex can be depressed when elicited repetitively at a frequency of ~1 Hz. This H-reflex depression is termed homosynaptic depression (HD) and is attributed to impaired neurotransmitter release from the presynaptic Ia terminal. In the present study, we systematically evaluated the extent to which HD in the soleus was modulated by the level of homonymous muscle contraction and the size of the test H-reflex. Changes in HD were also assessed while the target muscle was subjected to fatigue. The participants were 11 healthy male volunteers aged 20−25 years. HD was induced by delivering a percutaneous electrical stimulus at 1 Hz to the right posterior peroneal nerve. HD was proportional to the size of the test reflex size up to 60% of the maximum size of the direct motor response (Mmax), at which point values plateaued. HD decreased significantly during voluntary contraction of the homonymous muscle (range, <20% of maximal voluntary contraction [MVC]), irrespective of the degree of contraction. Within 1−5 minutes after completing 4 sets of the MVC for 60 s with ischemic arterial blockade, the degree of HD decreased significantly when the test reflex size was <60% of the Mmax. We conclude that test reflex size is a crucial factor when evaluating the nature of HD. Furthermore, HD reduction during voluntary contraction and muscle fatigue may represent an innate mechanism that serves to retain Ia transmission.